2020
DOI: 10.1039/c9sc04992d
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating nonadiabatic conical intersection dynamics by optical cavities

Abstract: Optical cavities hold great promise to manipulate and control the photochemistry of molecules. We demonstrate how molecular photochemical processes can be manipulated by strong light-matter coupling.For a molecule with an inherent conical intersection, optical cavities can induce significant changes in the nonadiabatic dynamics by either splitting the pristine conical intersections into two novel polaritonic conical intersections or by creating light-induced avoided crossings in the polaritonic surfaces. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 48 publications
2
93
0
Order By: Relevance
“…This strong cavity coupling results in the formation of hybrid field-matter states called dressed states or polaritons and consequently modifies the energy landscape of the molecules involved in the chemical process. 14 16 , 18 Tuning the resonance frequency of an optical nanocavity may in turn be used as a control knob for tuning the spectroscopic and dynamical properties of the molecular systems. 19 31 Notable examples of their potential applications include modifying the branching ratio between multiple reaction pathways, 32 controlling the photochemical reaction rates, 23 25 and improving Raman signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strong cavity coupling results in the formation of hybrid field-matter states called dressed states or polaritons and consequently modifies the energy landscape of the molecules involved in the chemical process. 14 16 , 18 Tuning the resonance frequency of an optical nanocavity may in turn be used as a control knob for tuning the spectroscopic and dynamical properties of the molecular systems. 19 31 Notable examples of their potential applications include modifying the branching ratio between multiple reaction pathways, 32 controlling the photochemical reaction rates, 23 25 and improving Raman signals.…”
Section: Introductionmentioning
confidence: 99%
“…The photochemistry of light-induced CIs is well explored 27 , 45 and recent studies have started to investigate the phenomena of cavity-field induced CIs. 13 , 14 , 46 Studies investigating the direct coupling of quantized light fields with the non-adiabatic dynamics of avoided crossings 15 or intrinsic CIs 16 , 47 are still limited. Previous studies have mainly considered polaritons formed by electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Recently, efforts have been made to study light-induced nonadiabatic phenomena in optical or microwave cavities. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] It has been successfully demonstrated that describing the photon-matter interaction with the tools of cavity quantum electrodynamics (cQED) [47][48][49][50] can provide an alternative way to study the quantum control of molecules with light. In this framework nonadiabatic dynamics arises due to the strong coupling between the molecular dofs and the photonic mode of the radiation eld which can alter the molecular energy levels by controlling the dynamics of basic photophysical and photochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29]34,35,42 As is already clear from classical light, quantum LICI situations can also only occur if, in addition to the only vibrational dof, the rotational angle between the molecular axis and the polarization vector of the electric eld in the cavity is also accounted for (in case of diatomics) 37,38 or at least two vibrational dofs are considered in the description. 26,44 Furthermore, quantum light-induced collective nonadiabatic phenomena (collective LICI) can also emerge when many molecules are involved in strong coupling to the cavity mode. 34,35,42 Our current aim is to study pure quantum light-induced nonadiabatic phenomena in a single polyatomic molecule placed in an optical nanocavity with methods ranging from a full-dimensional and accurate quantum-dynamical description to a simple one-dimensional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a classical laser field can induce a conical intersection even in a single diatomic molecule [35][36][37]. Indeed, a quantized radiation field also induces a conical intersection in a diatomic with new implications on its dynamic properties [38][39][40] and, of course, also in polyatomics [40,41]. New types of intersections appear when more molecules are subject to the same quantized field where the molecules interact with each other via the field.…”
mentioning
confidence: 99%